Trade Shocks and Labour Adjustment: Evidence from Pakistan’s Manufacturing Industries (The Pakistan Development Review, 2015)
The present study is an attempt to explore the impact of trade liberalisation on employment and wages of production and non-production workers in large scale manufacturing industries of Pakistan. We use a sample of 18 industrial establishments with a time series data covering a period 1970-71 to 2005-06. In order to account for endogeniety problem, this study uses the Generalised Method of Moments (GMM). The study comes up with the findings that trade liberalisation has significantly negative impact on employment of both production and non-production workers. On the other hand, trade liberalisation has a significantly positive impact on wages of production workers, but it has no significant impact on wages of non-production workers. The negative impact of trade is attributed to the high protection given to most of the inefficient industries in the post liberalisation period. On the other hand, reduction in non-production worker employment is not unexpected as in case of developing country like Pakistan, trade liberalisation is supposed to displace capital intensive industries that employ most of the non-production (skilled) workers. Keywords: Production Worker, Non-production Workers, Trade, Employment, Wages